Chronic obstructive pulmonary disease phenotypes: imprint on pharmacological and non-pharmacological therapy - Bakeer, Mostafa (Ann Transl Med, 2020)
Chronic obstructive pulmonary disease (COPD) is a heterogeneous disease associated with significant morbidity and mortality. Over the past few years, there has been cumulating interest in describing this heterogeneity and using this information to group patients into different COPD phenotypes. The term phenotype is defined as single or combination of disease attributes that describe differences between individuals with COPD as they relate to clinically meaningful outcomes. It describes also the physical appearance or biochemical characteristics which result from the genotype-environment interaction. Furthermore, it clearly identifies subgroups with a significant impact in the prognosis. Recently, approaches to COPD phenotyping have been significantly enhanced in tandem with developments in understanding the disease’s various pathological, clinical and genetic features. This knowledge inspired the researchers to investigate more tailored therapeutic strategies that could not only give a more potent effect but also help to avoid the traditional therapy’s undesirable side effects. Eventually, it could be said that the phenotypic approach to COPD in the last decade had a huge impact on daily practice and management delivered to COPD patients. In this review, we highlight the impact of pharmacological and non-pharmacological treatment options on COPD outcomes, using a personalized treatment strategy based on different phenotypes.